A systematic review and meta-analysis of cohort studies on the potential association between NAFLD/MAFLD and risk of incident atrial fibrillation - Zhou, Ben‐Gang; Ju, Sheng-Yong; Mei, Yu-Zhou; Jiang, Xin; Wang, Meng; Zheng, Ai-Jing; Ding, Yan-Bing (Frontiers in Endocrinology, 2023)
Background and aims: Recent cohort studies reported the association between non-alcoholic fatty liver disease (NAFLD) or metabolic-associated fatty liver disease (MAFLD) and atrial fibrillation (AF), but the results remained controversial and inconclusive. This meta-analysis aimed to explore this potential association. Methods: We systematically searched PubMed, Embase, and Web of Science databases to identify all relevant cohort studies investigating the association between NAFLD/MAFLD and AF published from database inception to October 30, 2022. Summary hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using random-effects models. Subgroup and sensitivity analyses were also performed. Results: A total of 13 cohort studies with 14 272 735 participants were included in our meta-analysis. Meta-analysis of data from 12 cohort studies with 14 213 289 participants (median follow-up of 7.8 years) showed that NAFLD was significantly associated with an increased risk of incident AF (HR = 1.18, 95% CI: 1.12-1.23, P ＜ 0.00001). Our subgroup analyses mostly yielded similar results, and the results of sensitivity analyses remained unchanged. However, meta-analysis of data from 2 cohort studies with 59 896 participants (median follow-up of 2.15 years) showed that MAFLD was not associated with incident AF (HR = 1.36, 95% CI: 0.63-2.92, P = 0.44). Conclusion: Current updated evidence shows that NAFLD is associated with a slight increased risk of incident AF. Nevertheless, we found insufficient evidence to support the proposed association between MAFLD and an increased risk of incident AF. To better clarify any association, future studies are need to take fully account of specific population, the severity of NAFLD/MAFLD, diagnostic methods of NAFLD and AF, and cardiometabolic risk factors. Systematic Review Registration: registration number: CRD42022371503.